Detection of Everyday Errors - Sellen, Abigail (Applied Psychology: An International Review (Special issue on error detection), 1994)
Although the study of errors has made an important contribution to our understanding of human action, the evaluation of action and the detection of slips have been largely ignored in psychology. In this paper, I examine the many ways in which errors were detected in a corpus of nearly 600 everyday slips and mistakes collected in a diary study. Using this collection, I propose a theoretical taxonomy of detection modes which aims broadly to describe the ways in which people realise their own errors in a wide variety of everyday tasks. The errors range from slips at the sensorimotor level, to memory lapses, to errors in judgement. The result is a general, descriptive framework within which to describe a range of detection mechanisms falling into three broad categories: Action-based detection, Outcome-based detection, and detection through Limiting Functions. The relation of type of error to detection mode, reasons for detection failure, and practical implications of the research are also discussed.